The big one : an island, an obsession, and the furious pursuit of a great fish - Kinney, David (David Francis) (New York, NY : Atlantic Monthly Press, 2009)
The Martha's Vineyard Striped Bass and Bluefish Derby is a five-week fishing tournament, but that description doesn't really do it justice. The derby, which has been held annually since 1946, is no mere fishing contest. It is, depending on the participant, a quest, a near-religious event, a self-affirmation, or just a chance to prove you can catch the biggest fish. In this lively book, Kinney combines a first-person account of a single derby with a history of the tournament itself (and it's a distinctly checkered history, with allegations of corruption and conspiracy, not to mention a few notable fatalities). He focuses on the personalities involved: the participants in the derby, the organizers, and the residents of Martha's Vineyard, who for five weeks every year see their island turned into what amounts to a staging area for a sea battle.
Includes bibliographical references.
Keywords: Tournament fishing -- Massachusetts -- Martha's Vineyard -- Anecdotes; Striped bass fishing -- Massachusetts -- Martha's Vineyard -- Anecdotes; Bluefishing -- Massachusetts -- Martha's Vineyard -- Anecdotes